2013
DOI: 10.1002/elps.201200402
|View full text |Cite
|
Sign up to set email alerts
|

Comparative proteomic and phosphoproteomic profiling of pancreatic adenocarcinoma cells treated with CB1 or CB2 agonists

Abstract: The pancreatic adenocarcinoma cell line Panc1 was treated with cannabinoid receptor ligands (arachidonylcyclopropylamide or GW405833) in order to elucidate the molecular mechanism of their anticancer effect. A proteomic approach was used to analyze the protein and phosphoprotein profiles. Western blot and functional data mining were also employed in order to validate results, classify proteins, and explore their potential relationships. We demonstrated that the two cannabinoids act through a widely common mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 57 publications
1
19
0
Order By: Relevance
“…Cannabinoids and their derivatives have recently attracted attention in the treatment of cancer due to their diverse abilities, including anti-inflammation, cell growth inhibition and antitumor properties ( 6 , 10 ). Previous studies have suggested that cannabinoid receptors may be an essential target for the treatment of cancer ( 14 , 15 ). Our previous study indicated that WIN-induced apoptosis of BEL7402 HCC cells may be mediated via the CB2 receptor; therefore, this receptor may be considered as a potential target for the treatment of HCC ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cannabinoids and their derivatives have recently attracted attention in the treatment of cancer due to their diverse abilities, including anti-inflammation, cell growth inhibition and antitumor properties ( 6 , 10 ). Previous studies have suggested that cannabinoid receptors may be an essential target for the treatment of cancer ( 14 , 15 ). Our previous study indicated that WIN-induced apoptosis of BEL7402 HCC cells may be mediated via the CB2 receptor; therefore, this receptor may be considered as a potential target for the treatment of HCC ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…The CB1 and CB2 selective agonists, arachidonylcyclopropylamide (ACPA) and GW, inhibited proliferation and invasion of Panc1 cells, respectively. 55 ACPA and GW through activating the CB1 and CB2 receptors stimulated 5' adenosine monophosphate-activated protein kinase activation via a reactive oxygen species (ROS)-dependent escalate of AMP/ATP ratio, causing cell autophagy and cell growth inhibition. 55,56…”
Section: Resultsmentioning
confidence: 99%
“…Spots were selected for identification based on significant differences in Student’t t -test ( p < 0.01) and/or good correlations [p(corr) > 0.75] by the multivariate OPLS-DA. Protein identification was performed after in-gel trypsin digestion, as previously described [ 29 ]. Briefly, peptides from each sample were separated by RP nano-HPLC-Chip technology (Agilent Technologies, Palo Alto, CA, USA) online-coupled with a 3D ion trap mass spectrometer (model Esquire 6000, Bruker Daltonics, Bremen, Germany).…”
Section: Methodsmentioning
confidence: 99%